Hydrogel polymer electrolytes toward better zinc-ion batteries: A comprehensive review - Jianwen Li; Alireza Azizi; Shuang Zhou; Sainan Liu; Chao Han; Zhi Chang; Anqiang Pan; Guozhong Cao (eScience)
Aqueous zinc-ion batteries (ZIBs) represent a promising solution for “beyond-lithium-ion” chemistries, but certain problems hinder their further development, especially when conventional aqueous electrolytes are involved. Hydrogel polymer electrolytes (HPEs) offer opportunities to circumvent these issues. This review aims to provide a fundamental understanding of how to design better HPEs for high-performing ZIBs, through critically analyzing the recent literature. Concerns regarding HPEs’ mechanical, interfacial, and electrochemical characteristics are addressed, followed by in-depth insights into their underlying mechanisms. Possibilities for practical applications of HPEs are also discussed.